Fundamentals of Cheese Science - Fox, Patrick F.; Guinee, Timothy P.; Cogan, Timothy M.; McSweeney, Paul L. H. (Springer US : Imprint: Springer, 2017)
This book provides comprehensive coverage of the scientific aspects of cheese, emphasizing fundamental principles. The book's updated 22 chapters cover the chemistry and microbiology of milk for cheesemaking, starter cultures, coagulation of milk by enzymes or by acidification, the microbiology and biochemistry of cheese ripening, the flavor and rheology of cheese, processed cheese, cheese as a food ingredient, public health and nutritional aspects of cheese, and various methods used for the analysis of cheese. The book contains copious references to other texts and review articles.